1978
DOI: 10.1159/000117650
|View full text |Cite
|
Sign up to set email alerts
|

HLA Typing and Affective Disorders: a Study in the Italian Population

Abstract: HLA phenotype distribution was investigated in 91 affective patients. Significant increases over those of the control population were found in HLA-A 29 and in Bw 22 frequencies, while A 10 and A 30 were decreased. No significant difference was shown between the two clinical subgroups (41 unipolar patients and 50 bipolar ones). On comparing our data with those from other authors, Bw 16 was significantly increased. However, a high degree of heterogeneity was also shown for this antigen. Of some interest is the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
4
9
0
Order By: Relevance
“…This is similar with the results of Smeraldi et al. 7 Although the statistical significance was marginal ( P = 0.051), there was a tendency for greater A3 frequency in patients with bipolar disorder, which could support the results of the study of Shapiro et al. 20 Smeraldi et al.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is similar with the results of Smeraldi et al. 7 Although the statistical significance was marginal ( P = 0.051), there was a tendency for greater A3 frequency in patients with bipolar disorder, which could support the results of the study of Shapiro et al. 20 Smeraldi et al.…”
Section: Discussionsupporting
confidence: 90%
“… 20 Smeraldi et al. reported that B22, being further divided into B54 and B55, had a greater frequency in patients with primary affective disorder 7 . In the present study, a greater B54 and lesser B51 frequency was found in the bipolar patient group before Bonferroni correction.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…These methods do not properly account for multigenerational information or for variable penetrance or for ascertainment through color blind Bipolar males, although the computa- , and reeent re ports have not supported the presence of any association (Temple et. al., 1979;Smeraldi, 1978;Beckman et. al., 1978).…”
Section: Studies O[ Chromosomallinkage In Bipolar Manic-depressivmentioning
confidence: 99%